Three‐dimensional product circularity. (13th February 2021) - Boyer, Robert H. W.; Mellquist, Ann‐Charlotte; Williander, Mats; Fallahi, Sara; Nyström, Thomas; Linder, Marcus; Algurén, Peter; Vanacore, Emanuela; Hunka, Agnieszka D.; Rex, Emma; Whalen, Katherine A.
Abstract: Understanding product circularity as "three‐dimensional" could anchor the Circular Economy to common principles while affording its followers flexibility about how to measure it in their specific sectors and disciplines and within their organization's means. Inspired by a heuristic developed for the urban planning profession to cope with the inherent conflicts of Sustainable Development, this article argues that measuring product‐level circularity should consider ways to achieve (1) high material recirculation, (2) high utilization, and (3) high endurance in products and service offerings. Achieving all three dimensions ensures that material flowing through the economy is recovered from prior use phases, that it is used intensely, and that it retains its value in spite of exogenous changes. The article argues further that these three dimensions ought to be measured and reported separately rather than as a composite metric and that certain applications will have opportunities to improve circularity through certain dimensions better than others. The article also explains how researchers at RISE (Research Institutes of Sweden AB) are working with industry and government partners to measure the three dimensions and how diverse actors interested in the Circular Economy can use the three dimensions to take the first steps in their transition to circularity.